Need Analysis of Teaching Materials for Kitabah Using the Genre-Based Pedagogy - Yasmar, Renti; Faisal Mahmud Adam; Umi Machmudah; Rahadian Kurniawan; Aidillah Suja (Institut Agama Islam Negeri Curup, 2025)
This study aims to analyze students' needs for Kitabah (Arabic writing) teaching materials through the lens of Genre-Based Pedagogy at IAIN Curup, Indonesia. Although Kitabah is a core component of language acquisition, its instruction remains heavily centered on grammar, with limited emphasis on developing coherent and meaningful texts. Employing a mixed-methods approach, data were gathered from 88 students and lecturers through a 5-point Likert scale survey, in-depth interviews, and classroom observations. The findings reveal that existing teaching materials lack structured guidance to support the progressive development of writing skills. Approximately 85% of students reported difficulties in writing independently, citing insufficient practice and a lack of constructive feedback from instructors. Moreover, the primary textbook used prioritizes grammatical forms over functional writing skills. This study recommends the development of instructional materials grounded in Genre-Based Pedagogy to enhance students’ ability to produce well-organized and purposeful texts. The findings contribute to Arabic language instruction by offering empirical insights for designing more effective Kitabah teaching resources. Theoretically, the study advances understanding of Genre-Based Pedagogy as applied to Kitabah instruction within the Indonesian context.